2007
DOI: 10.1002/sce.20202
|View full text |Cite
|
Sign up to set email alerts
|

Addressing nonscientific presuppositions in genetics using a conceptual change strategy

Abstract: ABSTRACT:Researchers are becoming aware of the influence of students' presuppositions in directing their construction of science concepts. When these are entrenched and drastically nonscientific, they predispose the children to alternative explanatory frameworks that are inhibiting, especially in a knowledge domain such as genetics. In this study, we identified such nonscientific presuppositions among 17-to 18-year-old secondary school students from the Igbo community of Southeastern Nigeria. We designed a res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Intervention studies involving genetics have been frequent (e.g., Araz & Sungur, 2007;Dogru-Atay & Tekkaya, 2008;Duncan & Reiser, 2007;Johnson & Stewart, 2002;Marbach-Ad, Rotbain, & Stavy, 2008;Mbajiorgu, Ezechi, & Idoko, 2007;Tsui & Treagust, 2007;Venville & Treagust, 1998). For instance, Tsui and Treagust (2007) reported that most of the participating students in Grades 10 and 12 improved their understanding of genetics in the development of genetic reasoning when teachers included computer multimedia in their classroom teaching.…”
Section: Intervention Studies Concerning Geneticsmentioning
confidence: 95%
“…Intervention studies involving genetics have been frequent (e.g., Araz & Sungur, 2007;Dogru-Atay & Tekkaya, 2008;Duncan & Reiser, 2007;Johnson & Stewart, 2002;Marbach-Ad, Rotbain, & Stavy, 2008;Mbajiorgu, Ezechi, & Idoko, 2007;Tsui & Treagust, 2007;Venville & Treagust, 1998). For instance, Tsui and Treagust (2007) reported that most of the participating students in Grades 10 and 12 improved their understanding of genetics in the development of genetic reasoning when teachers included computer multimedia in their classroom teaching.…”
Section: Intervention Studies Concerning Geneticsmentioning
confidence: 95%
“…Most studies consider only one perspective of conceptual changes in their model or theory: epistemological, ontological, or social/effective. However, more recently several researchers have studied conceptual change from multidimensional perspectives (Mbajiorgu, Ezechi, & Idoko, 2007;Savinainen, Scott, & Viiri, 2005;She, 2004b;Venville & Treagust, 1998). The Dual Situated Learning Model (DSLM) clearly shares the idea of multidimensional perspectives in terms of epistemology, ontology, and motivation.…”
Section: Perspectives Of Conceptual Change and Dual Situated Learningmentioning
confidence: 99%
“…Offspring inherit their biological parents' genes that express specific traits, such as some physical characteristics, natural talents, and genetic disorders. The mechanisms are hard to understand because it is difficult to make the ideas be tangible without the help of special instruments (Mbajiorgu, Ezechi and Idoko, 2006). The uses of the words genes, DNA, chromosomes, are interchanged in trying to explain how traits are passed from one generation to the next (Lewis and Kattmann, 2004).…”
Section: Introductionmentioning
confidence: 99%